Teacher educators as teachers and as researchers - Smith, Kari (2019)
[Excerpt] Teacher education has attracted many researchers over the years. It has also been subject to national and international debates about its goals and core features as well as issues of quality and effectiveness. Much has been written about ways of educating future teachers and the curriculum of initial teacher education in order to address the current and future needs of schools (Flores 2016). More recently, attention has been given to the work, identity and professional development of teacher educators. While there has been growing attention to teacher educators, existing literature points to divergent orientations and, to some extent, to lack of clarity regarding who they are, what they do, and how they develop professionally (Flores 2018; Ping, Schellings, and Beijaard 2018). Teacher educators are both teachers and researchers, a hybrid position which can be challenging to fulfill. The literature highlights the tensions between teaching and research in relation to time, competence, institutional and external demands, and not least, selffulfillment (e.g. Murray and Male 2005; Berry 2007; Loughran 2014; Kelchtermans, Smith & Vanderlinde, 2017). This special issue aims to present recent international research on how teacher educators, institutions and policy makers perceive, act on, and experience the dual responsibility teacher educators are required to develop. The collection of articles in this special issue address the topic of teacher educators as teachers and researchers in various countries and contexts, namely Australia, Belgium, England, Ireland, Israel, Portugal, Norway and USA. Collectively the authors examine the work of teacher educators considering their core mission, their professional development opportunities and the demands and needs of their working contexts. [...]